The inner workings of a hub-and-spoke cartel in the automotive fuel industry - Daniel Chaves; Marco Duarte (The University of Western Ontario, Department of Economics, 2021)
We analyze a hub-and-spoke cartel in the Brazilian automotive fuel industry. Using the court documents and detailed data on the supply chain we uncover three mechanisms beyond information sharing used by wholesalers (hub) to help retailers (spokes) solve the obstacles of price coordination: vertical transfers across asymmetric spokes; subsidies during punishment; and cost stabilization. We argue that wholesalers benefited from the cartel by being the exclusive supplier during the scheme. We use the synthetic control approach to quantify how successful the cartel was in increasing markups. We find that not only retailers, but wholesalers benefited from the cartel.
Keywords: K21; L12; D43; 330; Antitrust; Hub-and-Spoke Collusion; Vertical Restraints